The Influence of Organizational Factors and Customer Orientation on Hotel Performance through Hotel Customer Orientation Agility in Star-Rated Hotels in Central Java - Erny Kusmastuti; Denny Bernadus; Timotius Febry (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2026)
The hotel industry in Central Java faces intense competition due to increasing tourist destinations, rising customer expectations, and dynamic business environments. This condition requires hotels to develop customer-based strategic agility, known as Hotel Customer Orientation Agility, to enhance performance. This study aims to examine the influence of Organizational Factors and Customer Orientation on Hotel Performance, with Hotel Customer Orientation Agility as a mediating variable. A quantitative causal research design was employed using a survey of 134 managerial-level employees of five-star hotels in Central Java, selected through purposive sampling. Data were collected using a five-point Likert scale questionnaire and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS. The results show that Organizational Factors and Customer Orientation have a significant positive effect on Hotel Customer Orientation Agility. Customer Orientation has a significant direct effect on Hotel Performance, while Organizational Factors do not. Hotel Customer Orientation Agility has a significant effect on Hotel Performance and mediates the relationship between Organizational Factors and Customer Orientation with Hotel Performance. These findings indicate that hotel performance is enhanced primarily through customer-based agility rather than direct organizational effects, providing both theoretical insights and practical guidance for hotel management.